2022
DOI: 10.1007/s13205-022-03180-9
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium rhizogenes infection in threatened Indian orchid Dendrobium ovatum mobilises ‘Moscatilin’ to enhance plant defensins

Abstract: The present study illustrates the transformation ability of two wild-type bacterial strains of Rhizobium rhizogenes (MTCC 532 and MTCC 2364) on the embryogenic callus and callus-derived plantlets of a threatened Indian orchid, Dendrobium ovatum. Co-culture of the bacterium with the explants gave marginal hairy root phenotype that failed to multiply in the culture medium. Some primary and secondary metabolites were subdued in infected explants. Moscatilin, the stilbenoid active principle in D. ovatum, was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Recently, gastrodin was successfully transformed by ginseng hairy roots [ 85 ] and Datura stramonium hairy roots [ 86 ]. In the transformation experiment of D. ovatum hairy roots, it was found that enhancing the defense mechanism of plants can induce the synthesis of certain secondary metabolites [ 87 ]. Although this can enhance their defense mechanism, it also inhibits the formation of hairy roots.…”
Section: Conventional Methods For Increasing the Yield Of Secondary M...mentioning
confidence: 99%
“…Recently, gastrodin was successfully transformed by ginseng hairy roots [ 85 ] and Datura stramonium hairy roots [ 86 ]. In the transformation experiment of D. ovatum hairy roots, it was found that enhancing the defense mechanism of plants can induce the synthesis of certain secondary metabolites [ 87 ]. Although this can enhance their defense mechanism, it also inhibits the formation of hairy roots.…”
Section: Conventional Methods For Increasing the Yield Of Secondary M...mentioning
confidence: 99%